Education and the law (Longman Group, 1989)
"Information on all aspects of the law relating to primary, secondary, tertiary and higher education." T.p. verso.
Keywords: Educational law and legislation : Periodicals; Educational law and legislation; Great Britain : Education : Law : Serials